Demographic and clinical characteristics related to cognitive decline in Alzheimer disease in China: A multicenter survey from 2011 to 2014. Issue 26 (June 2016) - Peng, Dantao; Shi, Zhihong; Xu, Jun; Shen, Lu; Xiao, Shifu; Zhang, Nan; Li, Yi; Jiao, Jinsong; Wang, Yan-Jiang; Liu, Shuai; Zhang, Meilin; Wang, Meng; et al.
Abstract : Abstract: Alzheimer disease (AD) is the most frequent cause of dementia. AD diagnosis, progression, and treatment have not been analyzed nationwide in China. The primary aim of this study was to analyze demographic and clinical characteristics related to cognitive decline in AD patients treated at outpatient clinics in China. We performed a retrospective study of 1993 AD patients at 10 cognitive centers across 8 cities in China from March 2011 to October 2014. Of these, 891 patients were followed for more than 1 year. The mean age at diagnosis was 72.0 ± 10.0 years (range 38–96 years), and the mean age at onset of AD was 69.8 ± 9.5 years. Most patients (65.1%) had moderate to severe symptoms at the time of diagnosis, and mean Mini-Mental State Examination at diagnosis was 15.7 ± 7.7. AD patients showed significant cognitive decline at 12 months after diagnosis. Having more than 9 years of formal education was an independent risk factor related to rapid cognitive decline [odds ratio (OR) = 1.80; 95% confidence interval (95% CI): 1.11–2.91]. Early-onset AD patients experienced more rapid cognitive decline than late-onset patients (OR = 1.83; 95% CI: 1.09–3.06). Most AD patients in China had moderate to severe symptoms at the time of diagnosis and experienced significant cognitive decline within 1 year. Rapid cognitive decline in AD was related to having a higher educational level and younger age of onset.